Perbandingan Ratio Decidendi Putusan Mahkamah Konstitusi tentang Presidensial Threshold di Indonesia - Sam Meldrian Althonsius Oematan; Saryono Yohanes; Dhesy A. Kase (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The Constitutional Court (MK) regarding the Election Law on the presidential and vice presidential nomination threshold. Since the presidential election was held directly, the issue of the threshold for nominating presidential and vice presidential candidates has always surfaced every time a presidential election is held. In 2004, for example, the presidential nomination threshold was 10 percent. This research is a juridical-normative research, namely a process to find legal rules, legal principles, and legal doctrines in order to answer the legal issues faced. The data was analyzed descriptively-qualitatively.The results of this study indicate that the Constitutional Court Decision Number 74/PUU-XVII/2020 concerning the presidential nomination threshold (Presidential Threshold) is one of the important decisions in the discourse of democracy in Indonesia. The following is an explanation of the Ratio Decidendi of the decision in relation to the concept of democracy: Constitutionality of the Presidential Threshold The Constitutional Court (MK) in its decision emphasized that the presidential threshold or presidential nomination threshold is constitutional. This means that the provisions regarding the threshold do not conflict with the 1945 Constitution. The Constitutional Court is of the opinion that the presidential threshold is an open legal policy (Open Legal Policy) which is the authority of the lawmakers, namely the House of Representatives (DPR) and the President. The purpose of the Presidential Threshold, the Constitutional Court explained that the purpose of the presidential threshold is to simplify the party system and the presidential system, as well as to create government stability. The Ratio Decidendi of the Constitutional Court Decision Number 74/Puu-XXII/2024, Number 87/Puu-XXII/2024, Number 129/Puu-XXI/2023, Number 131/Puu-XXI 2023 concerning the Presidential Nomination Threshold is the Presidential Threshold is constitutional and does not conflict with the principles of democracy.